A CHARACTERISTIC STUDY OF POPAY ZIRCON SAND USED FOR CERAMICS, REFRACTORY AND FOUNDRY RAW MATERIALS - Lili Tahli; Tatang Wahyudi (Puslitbang tekMIRA, 2016)
The objective of this study is characterizing the zircon sand from Popay of Nanga Pinoh District, West Kalimantan as well as its performance when separated using physical method, i.e., tabling and magnetic separator in terms of obtaining zircon concentrate for making zircon flour. The satisfied requirement of zircon flour will be used for ceramics, refractory and foundry raw materials. Tabling followed by magnetic separator of Popay zircon sand increase zircon content from 43.54 to 65.50%. The content increases to 66.11% when reversing the process, namely started with magnetic separator and then tabling. Mineralogical analysis using optical microscope detected six minerals available within zircon sands. Those are zircon, ilmenite, magnetite, hematite, rutile and quartz while XRD analysis only identified five minerals. Hematite was not distinguished within Popay samples. Chemical analysis of the samples shows that the ZrO2 content within zircon flour is bigger than 65%. Such a figure is categorized as premium class for zircon flour to be used for refractory, ceramics and foundry.